Incidence of Vibrio metschnikovii in frozen fish products - Sanjeev, S; Varma, P R G; Mukundan, M K (Indian Journal of Fisheries, 2011)
Three hundred and twenty nine samples consisting of frozen fish and fish productscollected from processing factories in Kerala and Tamil Nadu were examinedfor the incidence of Vibrio metschnikovii. This organism was isolated from16.67% of IQF squid, 8.82% of frozen prawns, 2.38% of frozen squid and 2% ofIQF prawns. In general 3.34% of the samples were found to be carriers of V.metschnikovii. All samples of frozen fish fillets, frozen cuttle fish, frozen octopuswere found to be free from this organism. Informatioin regarding the incidenceof this organism in fish product is scanty. Hence this observation may berelevant to public health considerations of seafood consumption